Insights into Speaking Principles, Activities, and Materials in the English Language Education Department - hidayah nor; Muhammad Syahri (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2024)
Mastering speaking skills is crucial in learning a foreign or second language. Speaking is considered the most important element among the four main language skills. However, there are several discrepancies in the application of speaking principles, activities, and materials by educators in the English Education Department at various universities in Indonesia. Therefore, this study aims to identify the principles, activities, and materials lecturers use in teaching speaking courses. The research design employs a narrative inquiry approach. This study was conducted at Antasari State Islamic University Banjarmasin. The researcher conducted an interview with a speaking course lecturer. The interview provided data on applying principles, activities, and materials used in teaching speaking classes. Based on the objectives of this study, the researcher found that the lecturer applied four principles in teaching speaking: providing students with sufficient opportunities to practice fluency and accuracy, giving students chances to speak through group or pair activities while minimizing teacher intervention in the conversation, planning speaking tasks that involve negotiation of meaning, and creating classroom activities that involve instruction and practice in transactional and interpersonal speaking. Additionally, in conducting speaking activities, the lecturer used role play, simulation, and discussion. In the learning process, the lecturer frequently used audio-visual materials and PowerPoint presentations.